15.4k views
1 vote
Solve for p.

5p − 8(6p − 5) = p − 4

p =

2 Answers

4 votes

Answer:


p =(22)/(27)

Explanation:

5p - 8(6p - 5) = p - 4

-5p - 48p + 40 = p - 4

-53p + 40 = p - 4

-53p - p = -4 - 40

-54p = -44

p = 44 ÷ 54

p = 44/54

simplify with factor 2

p = 22/27

User Nujufas
by
5.6k points
6 votes

Answer:


p = 1

Explanation:


5p - 8(6p - 5) = p - 4


- 43p - 40 = p - 4


- 43p - p = - 40 - 4


- 44p = - 44


p = ( - 44)/(-44)


p = 1

Hope it is helpful.....

User Agent
by
6.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.